Avaliação clínica da infecção experimental de bezerros com Salmonella Dublin - Silva, D. G. [UNESP]; Silva, P. R. L. [UNESP]; Fagliari, J. J. [UNESP]; Ávila, Fernando Antonio de [UNESP]; Alessi, A. C. [UNESP]; Oliveira, R. G. (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2008)
The clinical conditions of healthy calves infected with experimental 10(8)CFU of Salmonella Dublin were evaluated and the viability of the experimental model in disease induction in calves was verified. Twelve 10 to 15-day-old male Holstein calves were examined. They were allocated into two groups, control and experimentally infected with 10(8)CFU of Salmonella Dublin. Animals were submitted to clinical examination after inoculation and at every 12 hours, during seven days after the experimental infection. Samples of rectal swabs were collected for Salmonella Dublin isolation. All animals had severe diarrhea, with mucus and bleeding, 12 to 84 hours after the experimental infection with Salmonella Dublin, accompanied by fever, dehydration and respiratory signs. The isolation of Salmonella Dublin from rectal swabs occurred 12 hours after the infection. Two out of the six animals inoculated with Salmonella Dublin died with symptoms of enteritis, fibrinous pneumonia, centrilobular hepatic steatosis, hepatocyte necrosis, spleen congestion, interstitial nephritis, and tubular degeneration. Thus, the oral administration of 10(8)CFU of Salmonella Dublin induced clinical signs of salmonellosis in 10 to 15-day-old calves.
Clinical evaluation of experimental Salmonella Dublin infection in calves
Keywords: Calf; Salmonella Dublin; salmonellosis; Bezerro; Salmonella Dublin; salmonelose